Integration and testing of autonomous rotorcraft UAV - Na, Shen Lee (2009)
This report provides a documented journey in rebuilding and reintegrating the systems of a severely damaged Rotomotion SR-20 UAV due to a crash. The report gives an understanding to the system, explaining in detail each subsystem found in the UAV. A discussion about the rotorcraft configuration of the SR-20 is presented. Based on the SR-20 rotorcraft platform, the basic theory of helicopter control including cyclic and collective pitch and how the control movements are achieved through the swashplate assembly, the role of Bell-Hiller flybar design in stabilization are also covered in the report. Also based on the SR-20 UAV, a performance analysis was carried out and discussed, and estimated performance of the SR-20 is being calculated. Upon completion of the rebuilding and reintegrating process, various tests and evaluations were carried out to test on different aspect of the UAV and evaluate the performance. The details of the tests and outcome including a successful flight test are documented towards the end of the report. And finally, some comments, caution remarks in operating the UAV in future as well as some suggestion on future work recommendation is presented in the final part of the report.